Fluctuations in Cd3+Subset Chimerism Are Not Predictive of Graft Rejection in Children Undergoing Transplant for Now Malignant Disorders - Ozyurek, E.; Cowan, M.; Koerper, M.; Baxter-Lowe, L. A.; Horn, B. (Elsevier Science Inc, 2008)
…
Annual Meeting of the American-Society-for-Blood-and-Marrow-Transplantation -- FEB 13-17, 2008 -- San Diego, CA